2016
DOI: 10.1021/acs.molpharmaceut.6b00089
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Net Negative Charge by Replacement of DOTA Chelator with DOTAGA Improves the Biodistribution of Radiolabeled Second-Generation Synthetic Affibody Molecules

Abstract: A promising strategy to enable patient stratification for targeted therapies is to monitor the target expression in a tumor by radionuclide molecular imaging. Affibody molecules (7 kDa) are nonimmunoglobulin scaffold proteins with a 25-fold smaller size than intact antibodies. They have shown an apparent potential as molecular imaging probes both in preclinical and clinical studies. Earlier, we found that hepatic uptake can be reduced by the incorporation of negatively charged purification tags at the N-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 57 publications
4
40
0
Order By: Relevance
“…Affibody molecules are non-immunoglobulin-based scaffold proteins characterized by high target specificity and binding affinity (Kd in the low-nanomolar to picomolar range) 52 , 53 . These small proteins have been generated against different cancer-associated molecular targets and have been labeled with different radionuclides ( 68 Ga, 18 F, 64 Cu, 99m Tc, and 111 In) suitable for immuno-PET and SPECT 54 - 59 . As for nanobodies, the half-life of fluorine-18 perfectly matches the fast pharmacokinetics of affibody molecules 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Affibody molecules are non-immunoglobulin-based scaffold proteins characterized by high target specificity and binding affinity (Kd in the low-nanomolar to picomolar range) 52 , 53 . These small proteins have been generated against different cancer-associated molecular targets and have been labeled with different radionuclides ( 68 Ga, 18 F, 64 Cu, 99m Tc, and 111 In) suitable for immuno-PET and SPECT 54 - 59 . As for nanobodies, the half-life of fluorine-18 perfectly matches the fast pharmacokinetics of affibody molecules 60 .…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously investigated the potential of radiolabeled affibody molecules as HER3-targeted imaging agents for PET and SPECT [15,16,[20][21][22]27]. It has been shown that an increase in the negative charge of the radionuclide-chelator complex can improve tumor-to-liver contrast for affibody molecules [26,36]. In addition, retention of activity in tumors is better than in normal tissues for several types of imaging probes.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that an increased negative charge can reduce unspecific hepatic uptake and, therefore, enhance the tumorto-liver contrast [27]. This hypothesis was further supported by comparing the effect of differently charged radiometal-chelator complexes on the biodistribution of ZHER3 labeled with 68 Ga and 111 In and HER2-targeting affibody molecules [26,31,36].…”
Section: Radiolabeling and Stability Assessmentmentioning
confidence: 96%
“…SKOV-3 tumor is always employed for evaluating the biologic properties of radiolabeled HER2 affibody due to abundant HER2 expression 33,34,35. Thus the HER2 targeting characteristic of 18 FAl-NOTA-MAL-MZHER 2:342 was initially determined using SKOV-3 models.…”
Section: Discussionmentioning
confidence: 99%